2009
DOI: 10.4314/as.v8i1.44110
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Degradation In Poultry Droppings And Cassava Peels-Amended Typic Paleustults In Southeastern Nigeria

Abstract: This greenhouse study was aimed at determining the potentials of poultry droppings (PD) and cassava peels (CP) for nutrient-enhanced biodegradation of petroleum hydrocarbon (THC) in a well drained Typic Paleustults using the THC levels and degradation duration as remediation indices. The performance of the organic amendments was compared against the performance of NPK fertilizer. The soil was contaminated with crude oil at the rate of 50 t/ha, after which the soil amendments were applied in single and combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…These differences between Bacillus species and Pseudomonas species are significant at p > 0.05. The result agrees with an earlier report by Jidere and Akamigbo [18]. In their report they stated that approximately 51% crude oil bioutilization was obtained after 20 days of incubation by Bacillus strains (28A and 61B) in an organic nitrogenous source.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These differences between Bacillus species and Pseudomonas species are significant at p > 0.05. The result agrees with an earlier report by Jidere and Akamigbo [18]. In their report they stated that approximately 51% crude oil bioutilization was obtained after 20 days of incubation by Bacillus strains (28A and 61B) in an organic nitrogenous source.…”
Section: Discussionsupporting
confidence: 92%
“…The study therefore affirmed that the presence and concentration of N 2 and P are critical in oil spill bioremediation campaign. Similar result was reported by Jidere and Akamigbo and Akamigbo and Jidere [18][19]. These authors stated that sufficient nitrogen and phosphorus are required to balance the available hydrocarbon in order for microbial growth and hydrocarbon reduction to occur.…”
Section: Discussionsupporting
confidence: 82%
“…The significant decrease in hydrocarbons (TPH and PAH) (p<0.05) and percent organic carbon (% OC), the significant increase (p<0.05) in microbial respiration (MCR) were potentially promoted in the earthworm treatment. Table 2 shows the Effect of number of earthworms on TPH degradation in the crude oil-contaminated soil, on day 0, 14 and 28 [26,29], portray similar results which states that physical actions (aeration, input of nutritionally-rich matters, bioturbation and increased soil surface area where responsible for microbial interaction), as previously reported by [27,29,31,33,34]. The 88-94% TPH level of reduction in the combined earthworms and mash treatment was in good agreement with the results published by [35], but was contrary only to the mixture ratio, where he concluded that such degree of reduction is obtainable only when 50% additive (compost) is used.…”
Section: Discussionsupporting
confidence: 69%
“…12 The undesirable ecological and socioeconomic effects associated with oil spills have led to the development of remediation techniques aimed at reducing the adverse effects of oil in the environment. 2 Biodegradation of hydrocarbon compounds is one of the most important processes involved in the weathering and ARTICLE eventual removal of oil from the environment, particularly for its non-volatile components. Thus, biodegradation can be used for the recovery of sensitive areas such as contaminated shorelines, marshes, and wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…The scale of the hazards imposed on the natural environment depends on the surface of the area contaminated by the petroleum products, their chemical composition, and the depth at which pollutants occur. [1][2][3][4] Crude oil causes a variety of risks when released into the environment. It is physically, chemically and biologically harmful to soil because of the presence of many toxic compounds, such as polycyclic aromatic hydrocarbons (PAH), benzene and its substituted and cycloalkane rings, in relatively high concentrations.…”
Section: Introductionmentioning
confidence: 99%